Comparison of Different Lecithin Diluents for Cryopreservation of Toraya Buffalo Semen - Riwu, R. M. J.; Arifiantini, R. I.; Karja, N. W. K. (Tropical Animal Science Journal, 2023)
The objective of this study was to compare the quality of frozen semen from Toraya buffalo with different lecithins from different commercial diluents. Fresh semen from two 6-9 years old Toraya buffaloes were collected once a week in the morning through an artificial vagina. Fresh semen was examined macroscopically and microscopically. Semen with more than 70% sperm motility was divided into three tubes, each diluted with Andromed (soy lecithin), Steridyl (egg yolk lecithin), and Bovifree (synthetic lecithin) diluents at a concentration of 100 x106 mL-1 motile sperm. The diluted sperm were placed in 0.25 mL straws and allowed to equilibrate for 4 hours. The sperm was frozen above liquid nitrogen favour for 15 minutes and stored in liquid nitrogen containers for further evaluation. The quality of frozen semen was assessed 24 hours after freezing. The parameters tested were motility, viability, abnormalities, plasma membrane integrity, and sperm recovery rate (RR). The results showed no significant differences in the values of motility, viability, abnormalities, plasma membrane integrity, and sperm RR in the three diluents used. Sperm motility values ranged from 45.93% to 47.09% after freezing. Sperm viability ranged from 56.21% to 60.27%. The values of membrane integrity of the three diluents used ranged from 57.73% to 61.36%. The values of sperm abnormalities after freezing and thawing ranged from 2.74% to 3.18%. In conclusion, three commercial diluents containing animal, vegetable, and synthetic lecithin bases can be used as diluents for freezing Toraya buffalo semen with similar results.